Pengaruh Kapasitas Kelembagaan Kelompok Tani Terhadap Kemandirian Petani di Kabupaten Gorontalo - Sry Yenni Pateda; Suparmin Fathan; Fauzan Zakaria (Jambura Journal of Animal Science, 2023)
This research aims to analyze the level of farmers' institutional capacity and the influence of institutional capacity on the independence of beef cattle farmers. This research was conducted in Gorontalo Regency from February to November 2018. The research used a survey method with a quantitative approach. The sample was determined in stages (multi stages sampling), namely by selecting districts, sub-districts, villages and groups. The determination of farmers as respondents was carried out in an exhaustive manner. The number of samples used was six groups with 120 group members. Data sources include primary and secondary data. The analysis used is descriptive analysis and quantitative analysis using structural equation modeling (SEM) statistics from the Analysis of Moment Structures (Amos) program. The research results explain the level of institutional capacity is good (3.18) which consists of indicators of goal achievement (3.24), institutional function and role (3.15), institutional innovativeness (3.12) and group institutional sustainability (3.18). Institutional capacity influences the independence of beef cattle farmers by 79%.